Factors Affecting Impulsive Buying Behavior - Raeni Dwi Santy; Ahmad Panji Mahendra; Yayah Sutisnawati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine the hedonic motives, Availability of Money, Impulse Buying of consumers who shop at the Marketplace and to determine the effect of hedonic motives and Availability of Money on Impulse Buying on consumers who shop at the Marketplace partially and simultaneously. The data will be analyzed using statistical tools and multiple regression analysis. Data collection uses purposive sampling by distributing online questionnaires to 100 registered consumers who have made online purchases in the ma rketplace. It is known that the results of this study explain that simultaneously and partially hedonic motives and the availability of money have a positive and significant effect on impulse buying. The conclusion of this study is that the hedonic motive is considered good, Availability of Money is considered good, Simultaneously, the hedonic motive and Avilability of Money have a significant effect on Impulse Purchases and are the influence of other variables not examined. Partially, the hedonic motif has a significant effect on Impulse Buying. Partially, Availability of Money has a significant effect on Impulse Buying. The impact of this study is to provide an overview of how impulsive buying can occur due to hedonic motives and the availability of money